2017
DOI: 10.1159/000484056
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nocturnal Noninvasive Ventilation on Pulmonary Rehabilitation in Patients with End-Stage Lung Disease Awaiting Lung Transplantation

Abstract: Background: Pulmonary rehabilitation (PR) in patients awaiting lung transplantation is crucial to ensure a transplant benefit. However, PR in patients with end-stage lung disease treated with noninvasive ventilation (NIV) remains an area of uncertainty. Objectives: The aim of the study was to assess the potential benefit of PR in patients awaiting lung transplantation treated with NIV. Methods: Patients awaiting lung transplantation who underwent comprehensive inpatient PR from 1998 to 2015 were retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Pulmonary rehabilitation (PR) including exercise training is a cornerstone modality of chronic obstructive pulmonary disease (COPD) management with a level ‘A’ evidence to improve exercise capacity, dyspnoea and quality of life . Promising evidences have shown that COPD patients with chronic hypercapnic respiratory failure (CHRF) may benefit from PR . However, their severely impaired clinical status and reduced capacity may restrain them in performing conventional exercise training including cycle endurance exercise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary rehabilitation (PR) including exercise training is a cornerstone modality of chronic obstructive pulmonary disease (COPD) management with a level ‘A’ evidence to improve exercise capacity, dyspnoea and quality of life . Promising evidences have shown that COPD patients with chronic hypercapnic respiratory failure (CHRF) may benefit from PR . However, their severely impaired clinical status and reduced capacity may restrain them in performing conventional exercise training including cycle endurance exercise.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Promising evidences have shown that COPD patients with chronic hypercapnic respiratory failure (CHRF) may benefit from PR. 3,4 However, their severely impaired clinical status and reduced capacity may restrain them in performing conventional exercise training including cycle endurance exercise. A number of studies have investigated the effects of noninvasive ventilation (NIV) as a supplemental tool during exercise with the goal of enabling exercise training at higher intensities not usually feasible for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, NIV is not expected to be beneficial in patients with kyphoscoliosis. During a specialised inpatient PR study, 296 of 1044 patients awaiting lung transplantation received nocturnal NIV due to hypercapnia 40. The increase in 6MWD after PR in the NIV group was higher, although by only 11 m. LTOT and NIV are potentially valuable therapeutic options, in particular to support patients with COPD with severe lung hyperinflation and exercise-induced oxygen desaturation41 in the context of exercise training as part of a comprehensive PR programme.…”
Section: Exercise Training Combined With Oxygen Supplementation or Nomentioning
confidence: 99%
“…Furthermore, despite more severe disease, patients under NIV had a greater benefit from rehabilitation than patients without NIV [31]. …”
Section: Exercise Training For Patients With Cvfmentioning
confidence: 99%